Odpowiedzi

2009-11-24T17:54:19+01:00
A)13 + 2x = 3
2x=13-3
x=5
b)-7 = 5x + 1
5x=-7-1
x= -5/8
c)7x - 21 = 5x
2x=21
x=21/2
d)6y - 13 = -52
6y=-52+13
y=-13
e)4x - 4 = 3
4x=7
x=4/7
f)3x + 2 = -70
3x=-72
x=-24
g) 33 - 4x = 4x
8x=33
x=33/8
h) 5 - 10x = -2x
-12x=5
x=-5/12

2 3 2
Najlepsza Odpowiedź!
2009-11-24T17:58:28+01:00
Oblicz x

a)13 + 2x = 3

13 + 2x = 3
2x = 3-13
2x = -10 /2
x = 5


b)-7 = 5x + 1

-7 = 5x + 1
-8 = 5x /5
⁸/₅ = x
1,6 = x


c)7x - 21 = 5x

7x - 21 = 5x
2x = 21 / 2
x = 11½


d)6y - 13 = -52

6y - 13 = -52
6y = 39 /6
y = ³⁹/₆
y = 6½


e)4x - 4 = 3

4x - 4 = 3
4x = 7 /4
x = 1¾


f)3x + 2 = -70

3x + 2 = -70
3x = -72 /3
x = 24


g) 33 - 4x = 4x

33 - 4x = 4x
33 = 8x /8
4¹/₈ = x


h) 5 - 10x = -2x

5 - 10x = -2x
5 = 8x /8
⁵/₈ = x
1 5 1
2009-11-24T18:29:37+01:00
A)2x=13-3
2x=10I:2
x=5
b)-5x=7+1I:(-1)
5x=-7-1
5x=-8I:5
X=⁸/₅
c)7x-5x=21
2x=21I:2
x=10,5
d)6x=-52+13
6x=-39I:6
x=-6⁵/₁₀
x=-6¹/₂
e)4x=4+3
4x=7I:4
x=⁷/₄
x=1³/₄
f)3x=-2-70
3x=-72I:3
x=-24
g)-4x-4x=-33
-8x=-33I:(-8)
x=4¹/₈
h)-10x+2x=-5
-8x=-5I:(-8)
x=⁵/₈
2 3 2